2015
DOI: 10.1080/00480169.2015.1064042
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive approach to lumbosacral decompression in a cadaveric canine model

Abstract: AIMS: To determine efficacy of a minimally invasive (MI) surgical approach using a human MI lumbar retractor for canine lumbosacral dorsal laminectomy and partial discectomy and to compare this technique to the standard open surgical (OS) approach.METHODS: Lumbosacral dorsal laminectomy and partial discectomy was performed on 16 largebreed canine cadavers using either a standard OS (n=8) or MI (n=8) approach. Skin and fascial incision length, procedure time, and intraoperative complications were recorded. Post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…A minimally invasive approach to the spinal canal has been reported in canine cadavers . In one study, a minimally invasive approach for a foraminotomy was evaluated, and in another study a minimally invasive approach for a corpectomy in the thoracolumbar spine was evaluated; both were endoscopically assisted .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A minimally invasive approach to the spinal canal has been reported in canine cadavers . In one study, a minimally invasive approach for a foraminotomy was evaluated, and in another study a minimally invasive approach for a corpectomy in the thoracolumbar spine was evaluated; both were endoscopically assisted .…”
Section: Introductionmentioning
confidence: 99%
“…Leperlier et al reported the use of a minimally invasive device with video assistance to perform ventral slot decompression in canine cadavers and in 10 clinical cases. A dorsal approach to access the lumbosacral space by using a minimally invasive retractor was described by Dent et al, showing equal access and decreased soft tissue disruption compared with a standard approach. Dent et al did not use an endoscope to improve visualization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard approaches to the spine, so called open techniques , involve muscle dissection from the bony elements with removal of ligaments, tendons, and bony structures, which are all important parts of the dorsal stabilizing element of the spine . Because of the frequency of spinal surgery in dogs, interest in MISS has been growing . However, most studies are limited to dog cadavers; only two reports have described MISS thoracolumbar technique in live dogs .…”
Section: Introductionmentioning
confidence: 99%
“…Benefits associated with MISS strategy include smaller incision, less soft‐tissue damage, less blood loss, lower complication rate, less scarring, less postoperative pain, quicker recovery, shorter hospital stay, and a quicker return to daily life activity . Although MISS is common practice in human neurosurgery, limited reports have been published on its use for the thoracolumbar spine in dogs . All these reports except one (percutaneous endoscopic pediculectomy) refer to canine cadavers.…”
Section: Introductionmentioning
confidence: 99%